STUDY OF FACTORS CAUSING DELAYS IN BUILDING PROJECT IMPLEMENTATION IN PASAMAN DISTRICT - Jamal, Akmal; Wardi, Wardi; Anif, Bahrul (Rang Teknik Journal, 2024)
Very important for contractor For finish work appropriate time, because matter That will profitable for owners, contractors, consultants and other parties who play a role in activities. And vice versa lateness work will very influential to reputation contractor. Objective study that is For Identify factors determine factor become dominant reason lateness implementation project buildings in the district Pasaman. Method research used that is method study in a manner quantitative that is with spread questionnaire to para respondent. Results research conducted there are 9 factors reason delay that occurred on project building in the District Passover that is that is factor Power Work, factor Managerial, Monitoring Evaluation factors, factors implementation Occupation, factor Location, factor Other, factor Characteristics Place, factor Environment, factor Constraint Implementation.